2020
DOI: 10.3389/fphar.2020.576496
|View full text |Cite
|
Sign up to set email alerts
|

Berberine Suppresses Colonic Inflammation in Dextran Sulfate Sodium–Induced Murine Colitis Through Inhibition of Cytosolic Phospholipase A2 Activity

Abstract: Ulcerative colitis (UC) causes chronic inflammation and damage to the colonic mucosal layer. Recent studies have reported significant changes in phosphatidylcholine (PC) and lysophosphatidylcholine (LPC) in UC patients and oral administration of PC has considerable therapeutic effects against UC, suggesting the metabolism of phosphatidylcholine may be involved in the UC development. Our previous work has demonstrated that berberine effectively suppresses inflammation and protects colonic mucosa injury in DSS-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 58 publications
3
22
0
Order By: Relevance
“…Western blot analysis were performed as our previously described ( 18 ). Used antibodies were listed as below: primary antibodies against p-AMPK (BS5003, Bioworld Technology, 1:1000), AMPK (BS1009, Bioworld Technology, 1:1000), RORγt (ab207082, abcam, 1:1000), GAPDH (2118S, Cell Signaling Technology, 1:1000) and anti-Rabbit IgG (7074S, Cell Signaling Technology, 1:2000).…”
Section: Methodsmentioning
confidence: 99%
“…Western blot analysis were performed as our previously described ( 18 ). Used antibodies were listed as below: primary antibodies against p-AMPK (BS5003, Bioworld Technology, 1:1000), AMPK (BS1009, Bioworld Technology, 1:1000), RORγt (ab207082, abcam, 1:1000), GAPDH (2118S, Cell Signaling Technology, 1:1000) and anti-Rabbit IgG (7074S, Cell Signaling Technology, 1:2000).…”
Section: Methodsmentioning
confidence: 99%
“…We infer that damp-heat syndrome may exacerbate the in ammatory response of IBD patients through LPCs. A previous report indicated that damp-heat syndrome was closely related to proin ammatory cytokines and typical medication to clear damp-heat would signi cantly reduce the LPC [43,44]. We suppose that LPCs might have the potential to become diagnostic biomarkers when the sample size increases in the future.…”
Section: Discussionmentioning
confidence: 85%
“…Cytosolic phospholipase A2a (PLA2G4A), an enzyme that hydrolyzes phosphatidylcholine to lysophosphatidylcholine, decreases in a colitis mouse model and in the inflammatory response of RAW 264.7 macrophages. Berberine binds to PLA2G4A directly and inhibits PLA2G4A activity by suppressing the MAPK/JNK signaling pathway to ameliorate colon inflammation ( Zhai et al, 2020 ).…”
Section: Antitumor Effects and Corresponding Mechanismsmentioning
confidence: 99%
“…In MKN-45-related gastric cancer, which harbors wild type p53, epiberberine shows great potential in inhibiting cell growth by inducing ROS, mitochondrial apoptosis and cell cycle arrest in vitro and inhibiting tumor growth in vivo via the p53/Bax pathway, and also inhibiting cell growth in the human gastric cancer (HGC-27) cells, which harbors mutated p53 ( Zhai et al, 2020 ). Lysine-specific demethylase 1 (LSD1) is considered a critical target in many cancer treatments ( Fiskus et al, 2014 ; Hong et al, 2018 ; Hu et al, 2019 ).…”
Section: Antitumor Effects and Corresponding Mechanismsmentioning
confidence: 99%